Aquaculture as a circular bio-economy model with Galicia as a study case: How to transform waste into revalorized by-products - Fraga-Corral, Maria (2018)
Background: World-wide aquaculture represents a very important sector capable of supplying huge amounts of animal protein. However its relevance has proportionally augmented its waste generation. In Europe, the geographical constitution of Galicia has prompted the instauration of many aquaculture-based systems along its coasts. Indeed aquaculture means a very relevant industry in Galicia, together with animal farming, agriculture and biotechnology. Scope and approach: Over the last decade Europe legislation encourages the proper management of wastes (mostly reutilization and reducing strategies) and the sustainable use of natural resources. The application of circular bio-economy (reuse of wastes) represents a feasible model to protect human and animal health and the environment. To achieve a more efficient production system that complies with European regulations, aquaculture wastes and sub-products need to be re-utilised to increase their throughput. This approach will positively impact on their economical yield while reducing their generation and thus protecting health and environment. Key findings and conclusions: Different applications have been considered for re-using aquaculture wastes and sub-products. One of the most efficient approaches is the establishment of models that allow the metabolic waste reduction, as the integrated multi-trophic aquaculture. For derived aquaculture sub-products, the most efficient process is recovering important biomolecules such as proteins (collagen, gelatine), polysaccharides (chitosan), lipids (omega 3) or pigments (astaxanthin or beta-carotene). Biomolecules can further be applied for human and animal consumption, food industry, cosmetics or pharmaceuticals. Due to the importance of this productive system in Galicia it is critical its update to include aquaculture into circular bio-economy.